Predictors of febrile urinary tract infection after ureterorenoscopy for urinary stones - D. H., Jayanth; Paul R., Fredrick; Gopi, Rayidi; Singh, Ravinder (International Surgery Journal, 2023)
Background: Ureterorenoscopy is a frequently used technique for the treatment of urolithiasis which provides high success rates when used under proper indications. Febrile urinary tract infection (FUTI) and urinary sepsis is the most frequent among its scarce complications. It often results secondary to urinary tract obstruction associated with urolithiasis, but also may occur after urinary tract manipulation such as ureterorenoscopy, clinical presentation varies from self-limited fever to the development of septic shock with the need for vasoactive agents or even to the patient’s death. This study has been designed to determine our rate of postoperative FUTI and sepsis after ureterorenoscopy, as well as to identify those factors that have been associated with its development. Method: Prospective study done on 219 patients who underwent ureterorenoscopy for urinary lithiasis in government medical college, Kottayam from February 2021-March 2022. Personal, clinical, surgical and microbiological data were collected. Patients who develop FUTI, urinary sepsis during 30 days following intervention were identified. Statistical analysis will be performed by chi squared test/fishers exact test; logistic regression as appropriate. Results: Our studies show incidence rates of postoperative FUTI in 11% and sepsis in 1.3%. Following statistical analysis, it was discovered that double J urinary diversion, a positive preoperative urine culture, diabetes, prolonged operational time, and intraoperative dilatation were all high-risk factors for the development of UTI after instrumentation. Conclusions: Ureteroscopy-associated urosepsis is a nosocomial infection. With the increasing popularity of ureteroscopic procedures, it is imperative that patients with increased risk are addressed appropriately, and suspected sepsis must be speedily and aggressively managed.